MHD mixed convection of nanofluid in a flexible walled inclined lid-driven L-shaped cavity under the effect of internal heat generation - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier, 2019)
In this study, mixed convective flow of nanofluid in an inclined L-shaped cavity which has elastic walls is numerically analyzed under the effects of internal heat generation and magnetic field by using the finite element technique with the Arbitrary-Lagrangian-Eulerian method. Simulations are performed for different values Richardson number (between 0.03 and 30), inclination angle of the cavity (between 0 degrees and 180 degrees), Hartmann number (between 0 and 50), orientation angle of the magnetic field (between 0 degrees and 90 degrees), internal Rayleigh number (between 10(4) and 10(6)), solid nanoparticle volume fraction (between 0 and 0.04), flexible wall elastic modulus (between 104 and 108) and aspect ratio (between 0.2 and 0.7) of the L-shaped cavity. It was observed that the effects of elastic wall on the convective heat transfer features are significant for the lowest value of Richardson number and lowest values of elastic modulus while 11% of discrepancy is obtained in the average Nusselt number when cavity with elastic and rigid walls is compared. The impact of the magnetic inclination angle is significant when compared to magnetic field strength for the variation of the average Nusselt number. Cavity inclination angle has significant impacts on the variation of the average Nusselt number for water and nanofluid. A higher size of the cold wall (aspect ratio) increases the heat transfer rate while the internal Rayleigh number reduces it. Enhancement in the average Nusselt number is about 15%-19% at highest nanoparticle volume fraction of the nanofluid while the trends in the convective heat transfer features with respect to changes in the pertinent parameters are similar for water and nanofluid. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Elastic wall; Internal heat generation; Nanofluids; Magnetohydrodynamics; Fluid-solid interaction; Inclined cavity